A theoretical investigation of topological phase modulation in carbide MXenes: Role of image potential states - Wang, Mengying; Ranjbar, Ahmad; Kühne, Thomas D.; Belosludov, Rodion V.; Kawazoe, Yoshiyuki; Liang, Yunye (Carbon, 2021)
MXenes have triggered great interests because of their potential applications. Depending on the exfoliation, MXenes can be terminated by O, F and OH groups. The properties of MXenes can be designed. Some F and O-terminated MXenes are predicted to be topological insulators (TIs). In OH-MXenes, the work-functions are significantly reduced. The image potential states (IPS), whose energies can be modulated by the interlayer distances, appear near the Fermi level. Based on the density functional theory, we study the electronic structures of the ordered double transition metal carbides multilayers M′2M”2C3(OH)2 (where M’ = V, Nb, Ta and M” = Ti, Zr, Hf) and investigate the role played by the IPS in the determination of the energy bands topology. For example, V2Ti2C3(OH)2 monolayer is a trivial semimetal. However, the layered V2Ti2C3(OH)2 becomes a strong TI by reducing the interlayer distance. In other words, the topological properties can be modulated. A novel energy band conversion involving IPS is proposed. Although the successful synthesis of M′2M”2C3(OH)2 MXenes faces plenty of challenges, the revealing topological transition mechanism will be valid for other materials whose IPS are near the Fermi levels. We expect that our prediction can advance the applications of low work-function multilayers as the controllable TI devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Image-potential states; MXenes; Topological insulator